ISSUING MEDICAL INSURANCE FOR THE PURPOSE OF EXTENDING THE LIFE OF THE POPULATION AND FURTHER IMPROVING DISEASE PREVENTION MEASURES - G. K. Dustova; F. X. O’rinboyev (Web of Journals Publishing, 2024)
Many people have a negative reaction to the word insurance, saying that it is a mandatory, useless thing, why is it necessary? Because in most cases, insurance is mandatory, and people buy insurance policies by paying appropriate amounts to insurance companies. It will show the services provided. Everything can be insured. Simply put, insurance means that we will protect you and provide guaranteed service for a certain amount.